Distributed Photovoltaic Architecture for HVDC-bus Feeding with a Simple Evaluation of Optimal Tracking. (August 2015) - Allouache, H.; Zegaoui, A.; Arab, M.; Belmadani, B.; Aillerie, M.
Abstract: This contribution describes, compares, and analyses two structures and their operating modes dedicated to renewable energy production from photovoltaic (PV) sources. Between the two different technical approaches, photovoltaic sources placed in a distributed architecture supplying a high DC voltage HVDC bus points large advantages. Thus, after preliminary comparison of both solutions and concluding phases, this efficient solution finally constitutes the main original analysis presented in this contribution. The distributed PV structure is investigated, implemented and simulated in an original way under the OrCAD/Pspice software environment. The adaptation stage for maximum power transfer is modelled in detail. A method to calculate the optimal duty cycle for optimal use of PV panels power is proposed, tested and validated by the use of a marketed PV module datasheet.